Intersectoral flows of technological knowledge in emerging countries: An input-output analysis - Eduardo Gonçalves; Amir Borges Ferreira Neto (CEPAL Review, 2016)
In this paper, we aim to assess the production, use and diffusion of technology in the production structure in emerging countries, such as Brazil, China, the Russian Federation and South Africa, through the analysis of: (i) users and producers of technology; (ii) research and development (R&D) content in each group of sectors, and (iii) technical knowledge flows between these groups. We use input-output matrices combined with sectoral R&D statistics to achieve our objectives. Our major findings point to significant differences among the emerging countries and also between developing and developed countries, including differences in sectoral hierarchy in terms of production and use of technological knowledge, and differences in the direction of main technological flows among sectors.